2000
DOI: 10.1002/1531-8249(200003)47:3<365::aid-ana13>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin‐1 gene polymorphisms with Alzheimer's disease

Abstract: Interleukin-1 (IL-1) is markedly overexpressed in Alzheimer's disease. We found the IL-1A 2,2 genotype in 12.9% of 232 neuropathologically confirmed Alzheimer's disease patients and 6.6% of 167 controls from four centers in the United Kingdom and United States (odds ratio, 3.0; controlled for age and for ApoE [apolipoprotein E] genotype). Homozygosity for both allele 2 of IL-1A and allele 2 of IL-1B conferred even greater risk (odds ratio, 10.8). IL-1 genotypes may confer risk for Alzheimer's disease through I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
81
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 18 publications
7
81
0
Order By: Relevance
“…IL-1a is markedly overexpressed in the brains of patients with Alzheimer's disease (AD). Several groups have reported that polymorphisms in the promoter regions of IL-1b and IL-1a increase the risk of AD [34][35][36][37], but these findings were not confirmed by others [38][39][40][41]. This controversy might be in part due to the difference in ethnic background between populations.…”
Section: Polymorphisms Of the Il-1 Clustermentioning
confidence: 99%
“…IL-1a is markedly overexpressed in the brains of patients with Alzheimer's disease (AD). Several groups have reported that polymorphisms in the promoter regions of IL-1b and IL-1a increase the risk of AD [34][35][36][37], but these findings were not confirmed by others [38][39][40][41]. This controversy might be in part due to the difference in ethnic background between populations.…”
Section: Polymorphisms Of the Il-1 Clustermentioning
confidence: 99%
“…Genes encoding proteins in inflammatory pathways might modulate risk for sporadic AD by increasing production of the protein and provoking a chronic inflammatory response in the brain with consequent neurodegeneration. A polymorphism in the promoter region [-889] of the interleukin-1A (IL-1A) has been shown to confer increased risk for AD [3,7,12], but other studies failed to replicate such an association [5,6,11], perhaps owing to the interaction of genetic modifiers in individual patients. The postulated common pathway of IL-1A and IL-8 in the cerebral inflammatory response [4,8] prompted us to examine the combined contribution of both genes to the susceptibility for AD.…”
mentioning
confidence: 99%
“…The AD and control samples were Caucasians originating from a homogeneous population in a limited geographical area in Northern Spain. The IL-1A [-889] and IL-8 [-251] polymorphisms were determined as described previously [9,12]. Association between dichotomous variables was analysed with odds ratio, and 95 % confidence intervals were estimated by the Cornfield method or the Fisher exact method.…”
mentioning
confidence: 99%
“…1B). In five of these studies [3-5, 9, 15] the OR of IL-1A 2/2 genotype associated with AD was < 1, in three studies [6,10,14] the OR was < 2, and only Nicoll et al [12] (OR 2.17, 95 % CI 1.04-4.54) and Combarros et al [1] (OR 2.43, 95 % CI 0.85-6.93) showed OR of higher than 2. The combined total of 1790 patients and 1981 controls from these ten studies were included in the metaanalysis, and using a fixed-effects model (P for homogeneity = 0.164), the pooled OR for AD associated with IL-1A 2/2 genotype was 1.21 (95 % CI 0.96-1.54, P = 0.112); likewise, no significant association was found using a random-effects model with a pooled OR of 1.19 (95 % CI 0.89-1.59, P = 0.231).…”
mentioning
confidence: 92%
“…Interleukin (IL)-1A is a potent proinflammatory cytokine that is markedly overexpressed in the brains of patients with AD [5,12]. A biallelic (allele 1 or low secretor of IL-1A, and allelel 2 or high secretor of IL-1A) polymorphism in the promoter (-889) region of the IL-1A gene might confer differential risk for the development of AD through modulating the production of IL-1A.…”
mentioning
confidence: 99%